2016
DOI: 10.1111/jeu.12332
|View full text |Cite
|
Sign up to set email alerts
|

Trichocysts—Paramecium's Projectile‐like Secretory Organelles

Abstract: This review summarizes biogenesis, composition, intracellular transport, and possible functions of trichocysts. Trichocyst release by Paramecium is the fastest dense core-secretory vesicle exocytosis known. This is enabled by the crystalline nature of the trichocyst "body" whose matrix proteins (tmp), upon contact with extracellular Ca , undergo explosive recrystallization that propagates cooperatively throughout the organelle. Membrane fusion during stimulated trichocyst exocytosis involves Ca mobilization fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 207 publications
(330 reference statements)
0
21
0
Order By: Relevance
“…Each zoochlorella cell was observed to be surrounded by multiple numbers of trichocysts, thus partially restricting its free horizontal transfer along the inner surface of the plasma membrane (Supplementary Movie 1). Previous reports on the ultrastructure of other non-symbiotic species of Paramecium showed that subcortical areas are mainly filled with trichocysts and mitochondria without zoochlorella 37, 38 .
Figure 2TEM analyses of the associations between P . bursaria mitochondria and symbiotic zoochlorella.
…”
Section: Resultsmentioning
confidence: 89%
“…Each zoochlorella cell was observed to be surrounded by multiple numbers of trichocysts, thus partially restricting its free horizontal transfer along the inner surface of the plasma membrane (Supplementary Movie 1). Previous reports on the ultrastructure of other non-symbiotic species of Paramecium showed that subcortical areas are mainly filled with trichocysts and mitochondria without zoochlorella 37, 38 .
Figure 2TEM analyses of the associations between P . bursaria mitochondria and symbiotic zoochlorella.
…”
Section: Resultsmentioning
confidence: 89%
“…). In Paramecium , these pumps would be too sluggish to mediate rapid Ca 2+ downregulation, for example, after massive exocytosis stimulation, thus stressing the importance of Ca 2+ binding to high‐capacity CaBPs (Plattner ,b). …”
Section: Specific Conservation and Changes During Evolutionmentioning
confidence: 99%
“…Since PMCA's working kinetics is rather sluggish, as found also in mammalian cells, PMCA was considered to serve mainly for household activity (Brini and Carafoli ). In Paramecium , balance calculations suggest that both P‐types pumps can regulate [Ca 2+ ] at best on a ~60‐min time scale (Plattner ,b). This makes both CaBPs and antiporter systems important for rapid [Ca 2+ ] i downregulation after stimulation.…”
Section: Specific Conservation and Changes During Evolutionmentioning
confidence: 99%
See 2 more Smart Citations